Functionally dissimilar neighbors accelerate litter decomposition in two grass species. Issue 3 (16th February 2017) - Barbe, Lou; Jung, Vincent; Prinzing, Andreas; Bittebiere, Anne‐Kristel; Butenschoen, Olaf; Mony, Cendrine
Summary: Plant litter decomposition is a key regulator of nutrient recycling. In a given environment, decomposition of litter from a focal species depends on its litter quality and on the efficiency of local decomposers. Both may be strongly modified by functional traits of neighboring species, but the consequences for decomposition of litter from the focal species remain unknown. We tested whether decomposition of a focal plant's litter is influenced by the functional‐trait dissimilarity to the neighboring plants. We cultivated two grass species ( Brachypodium pinnatum and Elytrigia repens ) in experimental mesocosms with functionally similar and dissimilar neighborhoods, and reciprocally transplanted litter. For both species, litter quality increased in functionally dissimilar neighborhoods, partly as a result of changes in functional traits involved in plant–plant interactions. Furthermore, functional dissimilarity increased overall decomposer efficiency in one species, probably via complementarity effects. Our results suggest a novel mechanism of biodiversity effects on ecosystem functioning in grasslands: interspecific functional diversity within plant communities can enhance intraspecific contributions to litter decomposition. Thus, plant species might better perform in diverse communities by benefiting from higher remineralization rates of their own litter.